2023
DOI: 10.3389/fpubh.2023.1214240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of public awareness and performance toward the safe use of household disinfectants-cleaners to prevent COVID-19 in the Emirate of Abu Dhabi

Nisreen Alwan,
Shatha Almazrouei,
Mariam Almazrouei
et al.

Abstract: IntroductionDisinfection is one of the most effective hygienic practices that would limit the spread of the Coronavirus Disease (COVID-19) through deactivating the coronavirus on contaminated skin, supplies, and surfaces. However, the type and concentration of disinfectants should be carefully selected to avoid damaging surfaces and to limit the side effects of these chemicals on household members and users. The aim of this study is to assess the public levels of awareness and performance concerning the safe u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Comparing the awareness scores among the sociodemographic variables, females, and highly educated participants (university levels) recorded higher scores of awareness than males and high school graduates. This is in congruence with the studies investigating the public awareness toward the preventive measures of COVID-19 in Saudi Arabia (36), and the public awareness toward the use of household cleaners-disinfectants during the spread of pandemic (35). The finding may be explained by the fact that women are primarily responsible for taking care of their homes and maintaining high levels of hygiene at the personal and household levels (37).…”
Section: Out Of 12) the Study Finding Indicates That Most Studysupporting
confidence: 84%
See 1 more Smart Citation
“…Comparing the awareness scores among the sociodemographic variables, females, and highly educated participants (university levels) recorded higher scores of awareness than males and high school graduates. This is in congruence with the studies investigating the public awareness toward the preventive measures of COVID-19 in Saudi Arabia (36), and the public awareness toward the use of household cleaners-disinfectants during the spread of pandemic (35). The finding may be explained by the fact that women are primarily responsible for taking care of their homes and maintaining high levels of hygiene at the personal and household levels (37).…”
Section: Out Of 12) the Study Finding Indicates That Most Studysupporting
confidence: 84%
“…Concerningly, many participants were unaware that the high-risk practices (e.g., sanitizing bare hands with bleach or other household cleaners or by using ultra-violet lamps) can damage skin tissues (33). Anticipating such high-risk practices to prevent COVID-19 was observed in a population-based studies in the UAE and USA (34,35). Similarly, literature studies focusing on university students showed awareness gap of the optimum temperature of water for effective handwashing and the necessary duration for hand disinfection (6,14).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the geographical location of Lebanon in Middle East (belonging to the Arabic culture), the community was expected to show similar levels of awareness and performance towards the hygiene-based preventive measures of COVID-19 compared to the studies of four Arabic speaking Middle Eastern countries (Jordan, Kuwait, Saudi Arabia, and United Arab Emirates) where participants embraced misconceptions about COVID-19, resulting in ineffective protective measures against SARS-CoV-2 infection [ 37 , 38 ]. However, in these studies, most of the study population showed a higher level of performance than awareness.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study from Abu Dhabi in the United Arab Emirates assessed public levels of awareness and performance concerning the safe use of household cleaning products and disinfectants during COVID-19. The results showed that the majority of survey respondents reported at least one adverse event associated with the use of disinfectants, ranging from skin irritation to poisoning, and significant differences in awareness and performance mean scores among various educational levels (p < 0.001) as well as the level of performance between males and females (p < 0.001) [4]. Additionally, studies from Italy and China showed toxicological events due to the mishandling of disinfectants [5,6].…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, the correct and appropriate application of household disinfectants for the optimal removal of pathogens within the home requires a reasonable understanding of how to correctly employ the disinfectant of the user within the home. Several reports have been published describing the role of household disinfectants during the pandemic [3,4]. One recent study from Abu Dhabi in the United Arab Emirates assessed public levels of awareness and performance concerning the safe use of household cleaning products and disinfectants during COVID-19.…”
Section: Introductionmentioning
confidence: 99%